Translation students’ conceptions of translation workflow in a simulated translation company environment - Konttinen Kalle; Veivo Outi; Salo Pia (Informa {UK} Limited, 2022)
Translation graduates need organisational skills to be able to cooperate in translation service production workflows. This paper explores the development of translation students’ workflow conceptions in a simulated translation company learning environment. Using the standard ISO 17100 as a frame of reference for a content analysis of student essays, two research questions are answered: 1) How does working in a simulated translation company learning environment affect translation students’ workflow conceptions? 2) What kind of workflow conception profiles emerge in a simulated translation company learning environment? A quantitative comparison of essays written before and after a one-year-long translation company simulation course showed a progression from rudimentary conceptions with few workflow task mentions towards more detailed conceptions that are closer to the translation industry model. Further quantitative analysis of the changes in individual task mention values revealed clusters of workflow tasks associated with the duties of two different task roles, the translation specialist and the project manager. The results showed a tendency for some students to stay with the conception associated with the translation specialist role and for some students to develop a workflow conception associated with the project manager role.